The Impact of an International Network (Gynecologic Cancer InterGroup) for Clinical Research on Global Capacity for Gynecologic Cancer Clinical Trials. Issue 4 (May 2017) - Stuart, Gavin C.E.; Kitchener, Henry C.; Vermorken, Jan B.; Quinn, Michael J.; Small, William; Pujade-Lauraine, Eric; Chou, Hansen; Wong, Michelle; Bacon, Monica
Abstract : Objective: The objective of this study was to demonstrate that the construction of the Gynecologic Cancer InterGroup (GCIG) has increased collaboration and accrual to high-quality phase 3 trials at a global level. Materials and Methods: The GCIG is a collaboration of 29 international cooperative clinical trial groups committed to conduct of high-quality phase 3 trials among women with gynecologic cancer. A complete bibliography of the reported phase 3 trials has been developed and is available on the GCIG Web sitehttp://www.gciggroup.com . A "GCIG trial" is a trial in which any 2 or more GCIG member groups are formally involved. We reviewed the output of the GCIG from 1997 to 2015 with respect to member participation and quality of publication (impact factor and citation index). The publications are considered in 3 cohorts, 1997 to 2002, 2003 to 2008, and 2009 to 2014, for the purposes of comparison and progress. A social network map has been developed for these publications to identify how the GCIG has increased capacity for clinical trials globally. Results: Using a global map, the number of member groups in the GCIG has increased in each of the 3 periods. The total annual number of publications and citations within the 1997 to 2015 period has increased significantly. The average number of citations per publication is demonstrated in each of the 3 periods. The steady increase in the number of citations is used as a proxy for the impact of the publications. The impact factor of the journal and the number of citations are reported for the 10 most highly cited publications. Finally, using a social networking methodology, networking has visibly and numerically increased in each of the 3 periods. Conclusions: Evidence supports that the construction of the GCIG has increased collaboration and accrual to high-quality phase 3 trials at a global level among women with gynecologic cancer.